Central Amygdala GluA1 Facilitates Associative Learning of Opioid Reward - Cai, You-Qing (Society for Neuroscience, 2013)
GluA1 subunits of AMPA glutamate receptors are implicated in the synaptic plasticity induced by drugs of abuse for behaviors of drug addiction, but GluA1 roles in emotional learning and memories of drug reward in the development of drug addiction remain unclear. In this study of the central nucleus of the amygdala (CeA), which is critical in emotional learning of drug reward, we investigated how adaptive changes in the expression of GluA1 subunits affected the learning process of opioid-induced context–reward association (associative learning) for the acquisition of reward-related behavior. In CeA neurons, we found that CeA GluA1 expression was significantly increased 2 h after conditioning treatment with morphine, but not 24 h after the conditioning when the behavior of conditioned place reference (CPP) was fully established in rats. Adenoviral overexpression of GluA1 subunits in CeA accelerated associative learning, as shown by reduced minimum time of morphine conditioning required for CPP acquisition and by facilitated CPP extinction through extinction training with no morphine involved. Adenoviral shRNA-mediated downregulation of CeA GluA1 produced opposite effects, inhibiting the processes of both CPP acquisition and CPP extinction. Adenoviral knockdown of CeA GluA2 subunits facilitated CPP acquisition, but did not alter CPP extinction. Whole-cell recording revealed enhanced electrophysiological properties of postsynaptic GluA2-lacking AMPA receptors in adenoviral GluA1-infected CeA neurons. These results suggest that increased GluA1 expression of CeA AMPA receptors facilitates the associative learning of context-drug reward, an important process in both development and relapse of drug-seeking behaviors in drug addiction.